Personality of perfect radiation therapy technologist (RTT) in patient’s opinion - Ossowska, Małgorzata; Majkowicz, Mikołaj (Psychoonkologia, 2010)
Wnioski : Pacjenci leczeni radykalnie oraz paliatywnie mają podobny pogląd na osobowość idealnego technika radioterapii. Czynniki społeczno-demograficzne, takie jak płeć i wiek pacjenta, mają znaczenie dla kształtowania się obrazu idealnego technika radioterapii. Abstract Background : The role of radiation therapy technologist (RTT) in therapeutic process should, beside irradiate patients, include psychological support in patient’s difficult time of treatment. The main aim of the study was to estimate expected personality features of “perfect RTT” depending on patient’s intent of treatment (palliative or definitive), demografical and clinical factors. Material and methods : Study group included 80 cancer patients (40 treated with palliative and 40 with radical intent) who underwent radiation therapy at the Department of Oncology and Radiotherapy, Medical University of Gdansk. Patients filled Adjective Check List (ACL) test questionnaire, and demographical/clinical questionnaire containing information on age, sex, civilian status, place of irradiation and number of fractions. Results : “The perfect RTT” should be organized, with perseverance, good self-control and personal adjustment. Quick behavioral changes, aggressive and excessive masculine behaviors were regarded as inappropriate. The preferred attitude of older patients (at least 65 years old) treated with radical intent and younger patients (below 65 years old) treated with palliative intent was a high level of need to care for patients. Older patients treated with palliative intent and younger patients treated with radical intent required “critical parent” attitude. Men from both groups (palliative and radical) required the attitude with a high level of need to care for patients. Conclusions : Cancer patients treated with palliative and radical intent have similar opinions about “perfect RTT” personality features. Preferred personality features showed some differences in relation to sex and age, whereas there was no relationship with civil status, area of irradiation and number of fractions.